Efficacy of a live intranasal vaccine against parainfluenza type 3 and bovine respiratory syncytial virus in young calves with maternally derived antibodies. Issue 1 (6th November 2020) - Metcalfe, Lucy; Chevalier, Mathieu; Tiberghien, Marie‐Pascale; Jolivet, Edmond; Huňady, Milan; Timothy, Sioned; Philippe‐Reversat, Corinne
Abstract : Trial design: Two randomised controlled vaccination trials with artificial challenges were carried out in addition to a serological survey of levels of maternally derived antibodies (MDA) to parainfluenza type 3 virus (PI3V) and bovine respiratory syncytial virus (BRSV) in European calves. Participants: Ten‐day‐old calves with and without MDA were included in the two vaccine trials. Interventions: Intranasal administration of a bivalent modified live (PI3V/BRSV) vaccine followed by artificial challenge approximately three months post vaccination. Objective: The study aimed to assess the efficacy of a modified live respiratory vaccine, Bovalto Respi Intranasal (Boehringer Ingelheim). In order to assess the interference of MDA, both seropositive and seronegative calves were used. Randomisation: PI3V and BRSV serological status was determined seven days before vaccination; calves without maternal antibodies became the MDA− vaccinates. Calves with MDA were ranked according to individual titres and allocated alternately to MDA+ vaccinate and MDA+ control groups. Blinding: Treatment was carried out by the unblinded study director. Animal care and veterinary examinations were conducted by personnel unaware of the treatments received. The serological survey used blood samples obtained from calves on commercial farms in five European countries, Germany, Spain, Italy, Ireland and the UK, to determine the levels of MDA to PI3V and BRSV in calves approximately two weeks of age. Results: A total of 36 calves were included in the two challenge studies and 32 of these completed the challenge studies. Twenty‐one calves were included in the PI3V challenge study, with six of six MDA− and six of seven MDA+ vaccinated calves and five of five MDA+ unvaccinated control calves being challenged with PI3V. Fifteen calves were included in the BRSV challenge study, with five of five MDA− and five of five MDA+ vaccinated calves and five of five MDA+ unvaccinated control calves being challenged with BRSV. Outcome: For both challenges, clinical scores and nasal shedding were significantly higher in control animals compared with vaccinates (PI3V challenge: clinical scores P=0.001, nasal shedding P=0.001; BRSV challenge: clinical scores P=0.016, nasal shedding P=0.002) and not significantly different between MDA+ and MDA− vaccinated animals for both challenges (P>0.05). A total of 254 samples from six countries were tested in the serological survey of MDA. Conclusion: The results of the challenge studies demonstrated the efficacy of the vaccine in the presence of BRSV and PI3V MDA under laboratory conditions. The field assessment confirmed that the MDA titres in the MDA+ calves corresponded to those typically found on farms.